2021
DOI: 10.3390/ma14227011
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Properties of Calcium Sulphoaluminate Cement as an Alternative to Ordinary Portland Cement

Abstract: This paper presents the results of research into the heat of hydration and activation energy of calcium sulphoaluminate (CSA) cement in terms of the dependence on curing temperature and water/cement ratio. Cement pastes with water/cement ratios in the range of 0.3–0.6 were tested by isothermal calorimetry at 20 °C, 35 °C and 50 °C, with the evolved hydration heat and its rate monitored for 168 h from mixing water with cement. Reference pastes with ordinary Portland cement (OPC) were also tested in the same ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…It can, therefore, be ascertained that the w/c ratio has a significant effect on the hydration heat and its development in CSA cement—to a lesser extend during early hydration, but to a high extend during the hardening phase. This effect is consistent with the previous tests of the CSA cement’s hydration [ 32 , 33 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It can, therefore, be ascertained that the w/c ratio has a significant effect on the hydration heat and its development in CSA cement—to a lesser extend during early hydration, but to a high extend during the hardening phase. This effect is consistent with the previous tests of the CSA cement’s hydration [ 32 , 33 ].…”
Section: Resultssupporting
confidence: 93%
“…On the other hand, the effect of the w/c ratio on early hydration has been thoroughly tested, and findings are similar across different research. An increased reaction rate of mortars with CSA and high w/c ratio was shown by research by Wang and Song [ 32 ], Gołaszewska et al [ 33 ], and Doval [ 30 ]. For Tang et al [ 34 , 35 , 36 ], the research results indicated an increase in the heat rate of CSA cements with a higher w/c ratio and, consequently, an increase in the temperature of the samples with increased water content.…”
Section: Introductionmentioning
confidence: 94%
“…The advantage of this mobile device is also the possibility of using it in field tests. Nevertheless, the comparative analysis shown in [32] indicates that in the case of thermal insulation materials, the accuracy of this method can be considered high only for the tested samples with a thickness of at least 100 mm. In the case of the lower thickness of the tested material, the obtained thermal conductivity may be overestimated, compared to steady-state measurement methods.…”
Section: Testing Methodsmentioning
confidence: 99%
“…There are several reasons for testing CSA cement as an alternative binder in foam concrete. First of all, CSA can be considered a more environmentally friendly material than OPC since the lower amounts of limestone involved in the production process, as well as lower burning temperature, generate reduced CO 2 emissions per 1 ton of clinker in comparison to Portland clinker [31,32]. Next, the properties of CSA cement such as short initial and final setting time as well as high early strength may be beneficial for the ultra-light foam concrete [32,33].…”
Section: Materials and Foam Concrete Mixturementioning
confidence: 99%
“…Sulfoaluminate cement (SAC) has been used for repairing roads and bridges due to its fast-hardening characteristics in recent years [11,12]. Feng's article points out that SAC mortar reinforced with ultra-fine steel fibers displays a maximum compressive strength (f cu ) of 19 MPa and flexural strength (f t ) of 5.3 MPa after curing for 3 h. SAC has excellent impermeability and corrosion resistance [13].…”
Section: Introductionmentioning
confidence: 99%